The Effectiveness of Augmented Reality-Based Learning Media on Students’ Conceptual Understanding of Science and Social Studies in the Solar System Topic at SDN Sanding 2 - Wulandari, Hesti; Nurulpaik, Iik; Sopandi, Wahyu; Triwahyuni, Ida (International Conference on Elementary Education, 2025)
Students' conceptual understanding of Natural Sciences and Social Sciences (IPAS) on the topic of the solar system is still low due to the dominance of conventional, non-interactive learning media. This condition highlights the need for technological innovations that provide contextual and engaging learning experiences. This study aims to test the effectiveness of Augmented Reality (AR)-based learning media in improving students' conceptual understanding. This study uses a quantitative approach with a quasi-experimental design, involving two sixth-grade classes at SDN Sanding 2, Petir District, with a total of 60 students. The experimental class used AR media, while the control class used conventional 2D images. Data were collected through pretest and posttest assessments. Data were analyzed using an independent t-test to determine the difference in the average score increase between the experimental and control groups, after first conducting a normality and homogeneity prerequisite test. The results of the independent t-test show that t_count = 5.92 > t_table = 2.00 with a p-value of 0.000, indicating a significant difference between the two groups. The average conceptual understanding score in the experimental class increased by 18.6 points, compared to 6.4 points in the control class. These findings indicate that Augmented Reality-based learning media effectively improves conceptual understanding and student engagement in learning about the solar system in elementary education.